(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The aim of the research is to determine and evaluate the repeatability of the robotic system by repeating the movements of the human hand, to identify the displacement using digital infrared projection equipment, skeletal methods and depth cameras. The article reviews and selects possible skeletal methods, motion recognition algorithms, reviews and substantiates the physical equipment selected for the technical stage of the experiment. The plan of experimental research stages, research stand, systematized research results, conclusions and usability suggestions are described.